a PHYTOPLANKTON BIODIVERSITY AND POLLUTION BIOINDICATOR IN BOJONEGARA COASTAL WATERS, BANTEN BAY, INDONESIA: Keanekaragaman Fitoplankton dan Bioindikator Pencemaran di Perairan Pesisir Bojonegara, Teluk Banten, Indonesia - sulistiono, sulistiono; Ronauli, Eva Cristine; Pertiwi, Niken Tunjung Murti; Effendi, Hefni (Universitas Jambi, 2022)
Coastal waters of Bojonegara in Banten Bay has a lot of pressure from the surrounding environment, including industry and sand mining. The high intensity and limited space encourage reclamation in coastal areas which can trigger changes in water quality. Research was conducted from October to December 2019, aims to analyze the phytoplankton biodiversity and pollution bioindicator of the waters. The phytoplankton was obtained through filtering 50 liters of water at a depth of 30 cm or surface waters. Observations were also made on water quality conditions including transparency, depth, color, temperature, pH, salinity, and dissolved oxygen (in-situ) and turbidity, Total Suspended Solid (TSS), nitrate, nitrite, and total phosphate (ex-situ). Data analysis was performed on abundance, diversity index, eveness and dominance, similarity index, and saprobic index. Based on observations, it is known that the phytoplankton found were in the class Bacillariophyceae, Chlorophyceae, Cyanophyceae, Dinophyceae, and Chrysophyceae. The index values of diversity, eveness, and dominance of phytoplankton each ranged from 0.2223-1.0070; 0,1289-0,5664; and 0.1550-0.8181, respectively. According to these values, the Bojonegara waters were classifeied as mild to moderate ecological pressure. The similar conditions are also indicated by the saprobic index values. The result of Main Component Analysis (PCA) shows the first component with 53.726% variance represented by turbidity parameters, TSS, total phosphate, transparency, depth, temperature, pH, and DO. These parameters have the most influence on the presence of phytoplankton.